A criminalidade organizada transnacional - Palma, Edgar António Ferreira da (2020)
The presente investigation takes transnational organized crime as its central axis, particularly with regard to the 1% biker groups, as a deep subculture of rules and values, making Portugal a coveted territory for its criminal activities. Transnational organized crime can include a varied number of ilegal organizations and activities that exist and occur all over the world, and in particular 1% biker groups, the object that is going to investigated, namely the criminal activities in which they have been involved and may constitute a threat to the society As research objectives, it is importante to understand the concept of transnational organized crime, to observe its legal framework at an international and later national level, to distinguish the concept of biker subculture, namely its history, structures, rules, and the vectors of identification, in order to understand their dissemination, interests and activities transnationally, and in particular those that may pose a threat to our country. The final objective will be to carry out a synthesis of what will be considered a threat to Portugal and to its internal security, and what are the existing mechanisms to try to combat this phenomenon, dominated by the urgency of intervention, in view of the threat they may represent. Methodologically, a set of techniques and instruments were mobilized to access information, carrying out a comprehensive bibliographic and documental research, trying to clarify the state of the art, giving privilege to monographs and reports available, in open sources, as well as a legislative analysis, for access to relevant meanings in order to better understand a subculture that at national level is still unknown by many, culminating in as analysis of episodes occurred and registered in national and international media sources about this subject.The challenges that arise in the future are many and diverse, and for that it is necessary to develop common, collaborative and coordenated forms of information exchange between law enforcement agencies and information services, allowing sharing efficient information, creating better conditions to prevent and intervene against transnational organized crime.It should be noted that the 1% biker groups, as relevant elements, emerging from recent experiences at national level from idiosyncratic trajectories, presente their own subculture and that can constitute a threat to the rule of law, according to the activities which they are connected and their way of being, due to the deviant behavior that they presente in analogy with the values of the current society. Recalling the recent events with 1%, biker groups, in general, violent episodes, for the dispute of territory and acts of revenge, with concerted and planned actions, without looking at the means to reach their objectives, we are undoubtedly facing a threat against the security and social peace, which is represents a huge challenges for national law enforcement agencies and intelligence services.